POLITIK IDENTITAS DAN FENOMENA BULLYING: TANTANGAN HAM DI ERA DIGITAL - Apriadi; Restika, Dea (KAGANGA KOMUNIKA: Journal of Communication Science, 2025)
The phenomenon of bullying has undergone significant changes in the digital age. What used to be limited to physical spaces like schools or communities has now shifted to cyberbullying that crosses social and geographic boundaries. This article discusses bullying as a new challenge in the digital era, adopting a human rights perspective. Bullying practices not only violate the rights to dignity and equality but also threaten global human security. The article analyzes how identity-based cyberbullying creates a dilemma between freedom of expression and protection from hate speech, using a review of literature and international documents that emphasize the need for global regulation. The findings show that digital-age bullying is a serious threat to human rights because of its anonymous, fast-spreading, and cross-border nature. Therefore, international policies, cooperation, and social diplomacy are necessary to strike a balance between free speech and the protection of individuals who are victims of discrimination. This article stresses that identity-based bullying in the digital age must be viewed as a human rights violation that requires a collective response across nations.   Keywords: Bullying, identity Politics, Digital Era, Human Rights.